Aureimonas mangrovi sp. nov., a marine alphaproteobacterium isolated from mangrove sediment in Thailand. Issue 7 (5th July 2021) - Huang, Hao; Punnarak, Porntep; Zhang, Qinghua; Piumsomboon, Ajcharaporn; Wang, Lei; Li, Weiwen; Chen, Shunyang; Chen, Guangcheng; Ou, Danyun
Abstract : Two bacterial strains, designated as 1-4-3 T and 1-4-4, were isolated from a mangrove sediment cultured with coastal seawater. The cells were Gram-stain-negative, motile, short, rod-shaped bacteria with flagella. Growth occurred at 4–37 °C, pH 7.0–9.0, and 0–7% NaCl. The predominant fatty acids of the novel strains were C18 : 1  ω7 c, C19 : 0 cyclo ω 8c, C18 : 0, and C16 : 0 . A phylogenetic analysis based on 16S rRNA gene sequences and whole genome phylogeny analysis based on distance matrix revealed an affiliation between the two strains and the genus Aureimonas, with closest sequence similarity to A. populi 4M3-2 T (96.41 and 96.64% similarity, respectively) and A. glaciistagni (96.01 and 96.23% similarity, respectively). The DNA G+C content of strain 1-4-3 T was 66.80 mol%. Strain 1-4-3 T displayed low DNA–DNA relatedness to A. populi 4M3-2 T, with an average nucleotide identity value of 77.47 % and digital DNA–DNA hybridization value of 22.83 %. Genotypic, chemotaxonomic, and phenotypic data indicate that strains 1-4-3 T and 1-4-4 represent a novel species of the genus Aureimonas, for which we propose the name Aureimonas mangrovi sp. nov. The type strain is 1-4-3 T (=LMG 31693 T =CGMCC 1.18507 T ).